Effect of acute sleep deprivation on left atrial mechanics assessed by three-dimensional echocardiography - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE; SARI, İBRAHİM; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (SPRINGER HEIDELBERG, 2016)
Although sleep deprivation (SD) affects cardiovascular system in many ways, physio-pathological changes in cardiac chamber volume and function have not been described well. The aim of the present study was to investigate the effect of SD on left atrial (LA) and ventricular function with three-dimensional (3D) echocardiography. Thirty-two healthy individuals (12 females, mean age 33.25 +/- 8.18) were evaluated. Echocardiographic examination was performed once after a night of regular sleep and a night of sleep debt. Beside conventional parameters, 3D phasic volumes and function were measured using a commercially available 3D echocardiography system and offline analysis software. Mean sleep duration of the study group was 8.15 +/- 2.19 h in the day of regular sleep and 2.56 +/- 2.25 h in the day of sleep deprivation. There was a significant prolongation in deceleration time (180.83 +/- 15.34 vs. 166.44 +/- 26.12; p = 0.044) and increase in E/e' (6.95 +/- 1.26 vs. 6.38 +/- 0.85; p = 0.005). Among 3D measurements, the difference in left ventricular ejection fraction (EF), LA EF, LA reservoir function and LA active EF were not significant. Mean LA passive EF of the individuals was significantly lower after night shift (24.10 +/- 7.66 vs. 31.49 +/- 7.75; p = 0.006). Acute SD is associated with a reduction in LA passive emptying function in healthy adults. 3D-derived indices were sufficient to show subclinical diastolic dysfunction according to impairment in passive phase of LA ejection. Prospective large-scale studies are needed to enlighten this issue.
Keywords: Sleep deprivation; Echocardiography; Left atrium; Left atrial volume; Diastolic dysfunction; HEALTHY-YOUNG ADULTS; STRAIN-RATE; CARDIOVASCULAR-DISEASE; STANDARDS COMMITTEE; OF-ECHOCARDIOGRAPHY; DIASTOLIC FUNCTION; BLOOD-PRESSURE; VOLUME; APNEA; QUANTIFICATION